2017
DOI: 10.1111/mve.12226
|View full text |Cite
|
Sign up to set email alerts
|

Sperm dimorphism in the Triatoma brasiliensis species complex and its applications

Abstract: Morphological and structural features of the sperm of the Triatoma brasiliensis Neiva, 1911 (Hemiptera: Reduviidae) species complex were examined in this first study investigating the sperm of Heteroptera and the genus Triatoma. Males were dissected and their seminal vesicles removed. For measurement, seminal vesicles were squashed on glass slides, spread, fixed and observed under a photomicroscope. The images were analysed and measures of sperm were made. Data were analysed using one-way analysis of variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The infraorder Cimicomorpha comprises 17 families, Miridae being the most specious, with more than 11,000 species (Weirauch & Schuh, 2011). However, only Reduviidae, Cimicidae and Anthocoridae had the sperm ultrastructure studied (Baffa et al, 2017; Báo & De Souza, 1994; Dallai & Afzelius, 1980; de Oliveira et al, 2019; Dolder, 1988; Santos & Lino‐Neto, 2018). The sperm of Pycnoderes incurvus (Bryocorinae) was previously described using light microscopy by Rezende et al (2021), which showed some interesting features worth further investigation (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The infraorder Cimicomorpha comprises 17 families, Miridae being the most specious, with more than 11,000 species (Weirauch & Schuh, 2011). However, only Reduviidae, Cimicidae and Anthocoridae had the sperm ultrastructure studied (Baffa et al, 2017; Báo & De Souza, 1994; Dallai & Afzelius, 1980; de Oliveira et al, 2019; Dolder, 1988; Santos & Lino‐Neto, 2018). The sperm of Pycnoderes incurvus (Bryocorinae) was previously described using light microscopy by Rezende et al (2021), which showed some interesting features worth further investigation (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In Heteroptera, many works that assess the morphology and morphometry parameters studied on the germ line cells, with a major focus on the spermatogenesis final processes (Araújo, Lino-Neto, Ramalho, Zanuncio, & Serrão, 2011;Araújo, Báo, & Lino-Neto, 2012;Baffa et al, 2017;Novais, Dias, & Lino-Neto, 2017;Santos & Lino-Neto, 2018). However, none of them presents focus in the TACs morphometry.…”
Section: Introductionmentioning
confidence: 99%